Should Treatment of Highly Differentiated Thyroid Carcinoma Be Conservative? - Biersack, H. J.; Helpap, B.; Koch, U.; Janson, R.; Baumgarten, C.; Winkler, C. (Nuklearmedizin - NuclearMedicine, 1983)
On the basis of three selected cases (one with clinically occult follicular and two with metastatic papillary carcinoma) the necessity of a comprehensive therapeutic concept even in highly differentiated thyroid cancer is stressed. Thyroid tissue and regional metastases should be eliminated by surgery, followed by radioiodine therapy in any event. Radiation teletherapy should be reserved to patients with invasive tumor growth exceeding the organ capsule, with lymph node metastases, and with massive angioinvasive growth.